PELAYANAN PENERIMAAN PESERTA DIDIK BARU (PPDB) ONLINE JENJANG SEKOLAH DASAR TAHUN PELAJARAN 2019/2020 DI DINAS PENDIDIKAN KABUPATEN GRESIK - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
The research objectives are to describe (1) the stages of implementing the Online New Student Admission Service (PPDB) for the Elementary School Level for the 2019/2020 Academic Year at the Gresik Regency Education Office; (2) Parents' Understanding of Online New Student Admission Services (PPDB) at Elementary School Level; (3) Utilization of Online New Student Admission Services (PPDB) at Elementary School Level by the Community. This research is descriptive qualitative. The results of the study show that the Online New Student Admission Service (PPDB) for the Elementary School Level for the 2019/2020 Academic Year at the Gresik Regency Education Office has been running well, in accordance with applicable rules and policies. In this Online New Student Admission Service Activity (PPDB), the local government's organizational culture is seen in the implementation stages, starting from the stipulation of the Activity Implementation Committee Decree, technical guidelines to the socialization of technical guidelines. The PPDB Online Technical Guidelines for the 2019/2020 Academic Year that have been set, are socialized to the public. With the aim that the public is better known and understands the policy, there are no obstacles when implementing PPDB Online. The PPDB Online system uses web-based technology so that it is easily accessible and transparent.